Napoleon - Weidhorn, Manfred, 1931- (New York : Atheneum, 1986)
A biography of the military genius who crowned himself Emperor of the French and whose empire covered most of western and central Europe.
Includes index.
Bibliography: p. 206.
Booklist.
8.3
Young Adult
Keywords: Napoleon -- I, -- Emperor of the French, -- 1769-1821 -- Juvenile literature; Napoleon -- I, -- Emperor of the French, -- 1769-1821.; Napoleon I, Emperor of the French; Generals; Kings, queens, rulers, etc; Generals; Kings and rulers; Queens; France -- History -- Consulate and Empire, 1799-1815 -- Juvenile literature; France -- Kings and rulers -- Biography -- Juvenile literature; France -- History -- 1789-1815.; France -- Kings, queens, rulers, etc